Risk assessment of individual landslide based on the risk acceptable model: a case study of the Shiyantan landslide in Mayang County, China. Issue 9 (20th October 2020) - Sui, Haoyue; Hu, Ruilin; Gao, Wei; Gao, Wenwei; Luo, Guanzhi
Abstract: Risk assessment and management of an individual landslide is the focus and difficulty. This paper analyzes the landslide losses in China from 1995 to 2018, combined with the ALARP approach, to research the risk acceptable model of landslide in China. Meanwhile, the Shiyantan landslide in Mayang county of Hunan Province is exemplified to quantitatively calculate the landslide risks under different conditions, and based on the risk acceptance level to judge whether the risk value is acceptable. The results show that the individual life risk acceptable criteria for Chinese landslide is 5.36 × 10 −6 /a, the upper and lower limits of the societal life risk (F-N curve) are 10 −7 /a and 10 −8 /a, the societal economic risk (F-D curve) are 10 −1 /a and 10 −3 /a. In addition, for the risk assessment of Shiyantan landslide, it is shown that the landslide may be damaged under extreme rainfall conditions. Its economic risk is tolerable risk and life risk is unacceptable risk. It is urgent to formulate relevant measures to mitigate the risk. The results can provide a reference for risk assessment and management conducted in other regions and offer a theoretical basis for early warning and forecast of landslide.